Retrospective analysis of volumes of manually expressed colostrum among healthy postnatal mothers at a tertiary care referral unit in South India. Not enough milk or not enough patience? - Vijay Kulkarni; Anita H Nyamagoudar; Netra S Kannur; Vinod Chavan (BMJ Publishing Group, 2024)
Introduction The volumes of colostrum have been quantified as 5 mL and 25 mL per feed on days 1 and 3, respectively, as per the data described about 20 years ago. However, the use of commercial formula is on the rise and 'not enough milk' is a common complaint by postnatal mothers.Objectives To determine the average volume of colostrum in one sitting per day on first three postnatal days among healthy late preterm and term gestational mothers and to compare the same among late preterm, term gestation and modes of delivery.Design Retrospective study.Setting A tertiary care perinatal setting in South India.Patients Healthy late preterm and term gestational mothers whose babies were roomed in.Interventions A lactation consultant helped the mothers manually express breast milk.Main outcome measures Volumes of manually expressed colostrum on first three postnatal days.Results Of the 391 mothers analysed in the study, on first three postnatal days, the average volume of colostrum in one sitting each was 4.68 mL, 8.87 mL and 22.53 mL, respectively. There was no statistically significant difference in volumes of colostrum secreted among term and late preterm mothers and also among mothers with different modes of delivery. As anticipated, multiparous mothers expressed significantly higher volumes as compared with primiparous mothers, on all three postnatal days.Conclusions The volumes of colostrum on first three postnatal days among healthy mothers were comparable with traditional volumes described about two decades ago. Gestational age and mode of delivery did not affect the volumes of colostrum in the present cohort.